Answer:
f(-1)=
[tex] \frac{ - 2}{3} [/tex]
f(2)=
[tex] \frac{1}{3} [/tex]
Step-by-step explanation:
let f(x)=f(-1)
but f(x) =3x+1
substituting it into the equation
3x+1=-1
3x=-1-1
3x=-2
dividing through by 3
[tex] \frac{3x}{3} = \frac{ - 2}{3} [/tex]
[tex]x = \frac{ - 2}{3} [/tex]
f(-1) =
[tex] \frac{ - 2}{3} [/tex]
f(2)
let f( x )=f(2)
then
3x+1=2
3x=2-1
3x=1
dividing through by 3
[tex] \frac{3x}{3} = \frac{1}{3} [/tex]
[tex] x = \frac{1}{3} [/tex]
f(2)=
[tex] \frac{1}{3} [/tex]
To find ƒ(2), substitute x = 2 into the Function ƒ(x) = 3x + 1. The answer is 7.
To find ƒ(2), we need to substitute x = 2 into the function ƒ(x) = 3x + 1.
Given: ƒ(x) = 3x + 1
Step 1: Substitute x = 2 into the function:
ƒ(2) = 3(2) + 1
Step 2: Perform the calculations:
ƒ(2) = 6 + 1
Step 3: Simplify the expression:
ƒ(2) = 7
First, substitute x = 2 into the function: ƒ(2) = 3(2) + 1 = 6 + 1 = 7.Therefore, ƒ(2) = 7.
Learn more about Function Evaluation here:https://brainly.com/question/35863537
#SPJ2
How does a 180 degree rotation about the origin change the coordinates of a shape
Answer:
According to the 180°-rotation rule, you take the OPPOSITE of both the x-coordinate and y-coordinate:
180°: [x, y] → [-x, -y]
I am joyous to assist you anytime.
What is the slope of a line perpendicular to the line whose equation is y=2x + 5?
slope=-1
slope =-1/2
slope=-2
Answer:
-1/2
Step-by-step explanation:
For a line to be parallel, they must be equal, for it to be prependicular, the slope must have an opposite value and be over the value.
Answer:
[tex]\frac{-1}{2}[/tex]
Step-by-step explanation:
General form of equation of line = [tex]y= mx+c[/tex]
Where m is the slope of line
We are given a line [tex]y=2x + 5[/tex]
On comparing with general form
m = 2
Let n be the slope of line perpendicular to the line [tex]y=2x + 5[/tex]
The product of the slopes of perpendicular lines is -1
So,[tex]m \times n = -1[/tex]
[tex]2 \times n = -1[/tex]
[tex]n = \frac{-1}{2}[/tex]
So, Option B is correct
Hence the slope of a line perpendicular to the line whose equation is y=2x + 5 is [tex]\frac{-1}{2}[/tex]
elena went bowling. elena's score in the first game was 127 she scored 16 more points in the second game than in the first game. wwhat was her total score?
Answer:
133
Step-by-step explanation:
127 + 16 = 133
. 50 cm =
0.005 of what
Answer:
It would be Meters, .50cm = 0.005 M
Order these numbers from least to greatest -1.264, -5/4,-1.015,-0.480,-14/25,-13/8
Andy and Sylvie each incorrectly simplified the expression -3 - 4(2x - 3). Andy wrote -14x + 21 and Sylvie wrote -8 - 6. Explain their errors and give the correct answer.
Answer:
Given the expression -3 - 4(2x- 3) the correct solution is -8x + 9.
Step-by-step explanation:
Andy wrote -14x + 21, so his error was to do de substraction (-3 -4) and then distribute -7(2x-3) = -14x+ 21.
Sylvie wrote -8x -6. Her error was to multiplied -4 only for 2x,
then -3 - 4(2x -3) = -3 -8x -3 = -8x -6.
Andy incorrectly distributed the negative sign and Sylvie made an error in simplifying the expression. The correct answer is -8x + 9.
Explanation:Andy's error: He incorrectly distributed the negative sign to both terms inside the parentheses. When distributing a negative sign to each term, the sign of each term should change. So, -4(2x - 3) becomes -8x + 12. However, Andy erroneously distributed the negative sign to only the first term, resulting in -14x + 21.
Sylvie's error: She incorrectly simplified the expression -8 - 6, which is equal to -14. However, this is not the correct result for the entire expression -3 - 4(2x - 3).
The correct answer is obtained by applying the distributive property and combining like terms. First, simplify the expression inside the parentheses: -4(2x - 3) = -8x + 12. Then, combine the terms outside the parentheses with the simplified expression: -3 - 8x + 12 = -8x + 9.
Learn more about Simplifying expressions here:https://brainly.com/question/36385368
#SPJ2
Find the area of the regular hexagon whose side length is 1 cm.
The area of the regular hexagon is approximately 2.598 cm².
Finding the Area of a Regular Hexagon
To find the area of a regular hexagon with a side length of 1 cm, we can use the formula for the area of a regular polygon:
Area = (3√3 / 2) × s², where s is the side length.
Given that the side length ( extbf{s}) is 1 cm:
Square the side length: 1² = 1 cm²
Multiply by (3√3 / 2): (3√3 / 2) × 1 cm² ≈ 2.598 cm²
Thus, the area of the regular hexagon is approximately 2.598 cm².
-3+9y=96 and 41=-3x+11
Answer:
y=11 x=-10
Step-by-step explanation:
Y:
Add 3 to both sides. Then divide by 9 on both sides.
X:
Subtract 11 from both sides. then divide by -3 on both sides.
Hope this helped
hELP ASAP WILL MARK THE BRAINLIEST!
Write the equation of the quadratic function with roots -10 and -8 and a vertex at (-9, -3)
Answer:
y = 3x² + 54x + 240
Step-by-step explanation:
The equation of a parabola in vertex form is
y = a(x - h)² + k
where (h, k) are the coordinates of the vertex and a is a multiplier
here (h, k) = (- 9, - 3), thus
y = a(x + 9)² - 3
To find a substitute either of the roots into the equation
Using (- 8, 0), then
0 = a(- 8 + 9)² - 3
0 = a - 3 ( add 3 to both sides )
a = 3
y = 3(x + 9)² - 3 ← in vertex form
Expand factor and simplify
y = 3(x² + 18x + 81) - 3
= 3x² + 54x + 243 - 3
= 3x² + 54x + 240 ← in standard form
Credit cards and charge cards differ in two important ways. One is the method of payment. What is the other difference?
A. You can get a credit card from your bank but not a charge card.
B. You have to pay interest on charge cards but not on credit cards.
C. You have to pay interest on credit cards but not on charge
Reset
NO
Find the of x in each triangle.
First, it is important to know that there are 180 degrees in a triangle. The equation for this is 90+3x=180, since the small square means 90 degrees. From there on, you should be able to figure it out yourself.
What is the product 7,000 x 50 written as the product of a whole number and a power of 10 ?
Answer:
[tex]7000\times 50 = 3,50,000 = 35\times 10^4[/tex]
Step-by-step explanation:
We have to find the product of 7,000 and 50 and express it in the form of product of a whole number and power of 10.
First, we will find the product.
[tex]7000\times 50 = 3,50,000[/tex]
Now, we have to express this product as a sum of whole number and power of 10.
3,50,000 can be written as:
[tex]3,50,000 = 35\times 10^4[/tex]
Here, 35 is our whole number and [tex]10^4[/tex] is required power of 10.
We used the rule of exponents to express the product in such manner.
Which of the following statements uses the commutative property of addition?
2 + (3 + 4) = (2 + 3) + 4
2 + (3 + 4) = (2+ 3) + (2 + 4)
2 + (3 + 4) = 2 + (4 + 3)
The statement 2 + (3 + 4) = 2 + (4 + 3) is the one that uses the commutative property of addition, which states that changing the order of numbers being added does not affect the sum. So correct answer is first option.
The statement that uses the commutative property of addition is 2 + (3 + 4) = 2 + (4 + 3). The commutative property of addition states that the order in which two numbers are added does not change the sum.
This is represented by the equation A+B=B+A. In our specific example, changing the order of 3 and 4 does not affect the sum when added to 2.
This demonstrates the commutative property in a clear manner.
Azeneth is putting a fence around her rectangular garden. The width of the garden is 4x + 5 ft. and the
length is 2x^2 – 3x + 7 ft.
How much total fencing does Azeneth need to buy in terms of x?
Answer:
Azeneth needs to buy 4x² + 2x + 24 feet
Step-by-step explanation:
* Lets explain how to solve the problem
- Azeneth is putting a fence around her rectangular garden
- The width of the garden is 4x + 5 feet
- The length is 2x² – 3x + 7 feet
- We need to find how much total fencing Azeneth needs to buy in
terms of x
∵ The fence will put around the four sides of the rectangular garden
∴ The length of the fence is equal to the perimeter of the garden
- The perimeter of any rectangle = 2l + 2w, where l and w are its
dimensions
∵ The perimeter of the garden = 2 × its width + 2 × its length
∵ Width = 4x + 5
∴ 2 × width = 2(4x + 5) = 8x + 10
∵ Length = 2x² - 3x + 7
∴ 2 × length = 2(2x² - 3x + 7) = 4x² - 6x + 14
∴ The perimeter of the garden = 8x + 10 + 4x² - 6x + 14
- Add like terms
∴ The perimeter of the garden = 4x² + (8x - 6x) + (10 + 14)
∴ The perimeter of the garden = 4x² + 2x + 24
∵ The length of the fence = the perimeter of the garden
∴ The length of the fence = 4x² + 2x + 24 feet
* Azeneth needs to buy 4x² + 2x + 24 feet
Jackie brought 3/4 of a gallon of iced tea to the party. Bill brought 7/8 of a gallon of iced tea to the same party. How much iced tea did Jackie and Bill bring to the party?
Answer:
[tex]\frac{13}{8}=1\frac{5}{8}[/tex] gallons
Step-by-step explanation:
We have been given that Jackie brought 3/4 of a gallon of iced tea to the party. Bill brought 7/8 of a gallon of iced tea to the same party.
To find the total amount of iced tea, we will add both quantities as:
[tex]\text{Amount of ice tea brought to party by Jackie and Bill}=\frac{3}{4}+\frac{7}{8}[/tex]
Make a common denominator:
[tex]\text{Amount of ice tea brought to party by Jackie and Bill}=\frac{3*2}{4*2}+\frac{7}{8}[/tex]
[tex]\text{Amount of ice tea brought to party by Jackie and Bill}=\frac{6}{8}+\frac{7}{8}[/tex]
Add numerators:
[tex]\text{Amount of ice tea brought to party by Jackie and Bill}=\frac{6+7}{8}[/tex]
[tex]\text{Amount of ice tea brought to party by Jackie and Bill}=\frac{13}{8}[/tex]
[tex]\text{Amount of ice tea brought to party by Jackie and Bill}=1\frac{5}{8}[/tex]
Therefore, Jackie and Bill brought [tex]\frac{13}{8}=1\frac{5}{8}[/tex] gallons of ice tea to the party.
Write an algebraic expression for the phrase.
the sum of b and 11
a. b – 11
b. b/11
c. b + 11
d. 11b
Final answer:
The algebraic expression for the phrase 'the sum of b and 11' is 'b + 11'. This expression represents adding 'b' to '11', and addition is commutative, which means it could also be written as '11 + b'. So the correct option is c.
Explanation:
The phrase 'the sum of b and 11' represents an algebraic expression where sum refers to the addition of two terms. When we talk about the sum of two algebraic expressions, we use the plus sign (+) to denote the operation. Therefore, for the given phrase 'the sum of b and 11a', the algebraic expression is b + 11.
It’s important to keep in mind that in algebra when we want to indicate that one term is multiplied by another, we often place them next to each other without any symbol, which is known as concatenation. And because addition is commutative, we could also write this expression as 11 + b, and it would mean the same thing.
Also worth mentioning is the distinction between the expression 'b - 11' (which means 'b' subtracted by '11') and 'b/11' (which means 'b' divided by '11'). These are different operations and would not correctly represent the phrase we were given to translate into an algebraic expression.
vertices que tiene el prisma hexagonal
Answer:
12
Step-by-step explanation:
in geometry, the hexagonal prism is a prism with hexagonal base. This polyhedron has 8 faces, 18 edges, and 12 vertices. Since it has 8 faces, it is an octahedron. However, the term octahedron is primarily used to refer to the regular octahedron, which has eight triangular faces.
(se poquito de espanol, lo lamento)
I need help please???
Answer:
63
Step-by-step explanation:
51 - ( - 12) (-)(-)=(+)
51 + 12
63
Answer:
63
Step-by-step explanation:
The question says 51 +12 becase two negatives make a positive.
If s(x) = 2 - x and f(x) = 3x, which value is equivalent to (s f) (-7)
The equivalent value for (s \\circ f) (-7), given s(x) = 2 - x and f(x) = 3x, is 23.
The question asks which value is equivalent to (s \\circ f) (-7), where s(x) = 2 - x and f(x) = 3x.
To solve for (s \\circ f) (-7), we first need to find f(-7). Since f(x) = 3x, we substitute x with -7:
f(-7) = 3(-7) = -21.
Next, we calculate s(f(-7)), which means we substitute x in s(x) with the value of f(-7):
s(-21) = 2 - (-21) = 2 + 21 = 23.
Therefore, the equivalent value is 23.
Drag the tiles to the correct boxes to complete the pairs. Not all tiles will be used.
Match each situation to its corresponding expression.
Answer:
150(0.4),2,500(0.11)
Step-by-step explanation:The first question says 150 participants and 40%of the participants are eliminated. so it's 150(0.4)n
same goes for the second 2,500 bacteria in a colony the colony grows at a rate of 11% every hour so the answer to the question is 2,500(0.11)n
The student is tasked to match situations with their corresponding mathematical expressions, identifying key mathematical operations and formulating accurate representation for these operations
Explanation:The question is asking you to match given situations with their corresponding mathematical expressions. An example might be the situation 'Tom has twice as many apples as Tim' being matched to the expression '2T', where 'T' denotes the number of apples Tim has. To solve this, read each situation carefully and identify the key mathematical operations (addition, subtraction, multiplication, division) or relationships (equal to, greater than, less than) embedded within them. Then, formulate a mathematical expression that accurately represents these operations or relationships.
For example, if the situation is 'Sally has five more books than John,' the corresponding mathematical expression might be 'J+5' with 'J' representing the number of books John has.
Learn more about Mathematical Expressions here:https://brainly.com/question/34902364
#SPJ2
For } (x) = 3x + 1 and g(x) = 72-6, find (f + g)(x).
the answer is f (-3x - 22) = -6x - 33
math help pls!! will reward : )
Good evening ,
______
Answer:
A. x=all real numbers.
D. x = [tex]\frac{2-np}{2}[/tex]
___________________
Step-by-step explanation:
25-5x=5(-x+5)
25-5x=-5x+25
25-5x=25-5x
Then this equation is valid for all real number x
Note : If you replace x by any number you will get 0 = 0 and that always true.
:)
Answer:
a
Step-by-step explanation:
Mary invested 5,000 into a bank account that was earning 2.5 percent interest compound monthly what would her exact account balance be after 3 years?
Answer:
$12,162.68
Step-by-step explanation:
It's compounded monthly. 3 years is 36 months.
A = P (1 + r)^n
A = 5000 (1 + 0.025)^36
A ≈ 12162.68
Rounded to the nearest cent, her exact account balance would be $12,162.68.
Madden and Jenn both worked at the coffee shop today. Madden's total cups of coffee made is represented by f(x); and Jenn's total cups of coffee made is represented by g(x). Use the functions below to write a function that represents the total cups of coffee they made today.
f(x) = 7x − 4
g(x) = 5x + 1
A. 9x + 5
B.9x − 3
C.12x + 5
D.12x − 3
Answer:
The answer is D. 12x - 3.
Step-by-step explanation:
To add these functions, we just add the terms.
f(x) + g(x) = (7x - 4) + (5x + 1)
7x - 4 + 5x + 1 | Simplify
7x + 5x - 3
12x - 3.
Answer:
Option D. (12x - 3)
Step-by-step explanation:
Madden's total cups of coffee made is represented by the function f(x).
f(x) = 7x - 4
Jenn's total cups of coffee made is represented by the function g(x).
g(x) = 5x + 1
Now we have to write a function that represents the total cup of coffee that represents they made.
That will be represented by f(x) + g(x) = (7x - 4) + (5x + 1)
f(x) + g(x) = 12x - 3
Therefore, option D. will be the answer.
Tonka weighs 150 lb. He is loading a freight elevator with identical 67-pound boxes. The elevator can carry no more than 2000 lb. If Tonka rides up with the boxes, how many boxes can be loaded on the elevator?
Final answer:
Tonka can load a maximum of 29 boxes on the elevator.
Explanation:
To calculate the number of boxes Tonka can load on the elevator, we need to divide the maximum weight capacity of the elevator by the weight of each box. The weight capacity of the elevator is 2000 lb, and each box weighs 67 lb. Therefore, the number of boxes Tonka can load is found by dividing 2000 lb by 67 lb:
Number of boxes = 2000 lb ÷ 67 lb = 29.85
Since we can't have a fraction of a box, Tonka can load a maximum of 29 boxes on the elevator.
What is the slope of x=18?
Answer:
Ø
Step-by-step explanation:
Anything that is set to equal x is what is known as an undefined rate of change [slope] because it is a vertical line.
I am joyous to assist you anytime.
Simplify
(2/3 +1/6) please
brnialest
.
Answer:
5/6
Step-by-step explanation:
Hey!
------------------------------------------------
Steps To Solve:
~Find common denominators
2/3 = 4/6
1/6
~Add
4/6 + 1/6
~Simplify
5/6
This cannot be simplified.
------------------------------------------------
Answer:
5/6
------------------------------------------------
Hope This Helped! Good Luck!
If Carl was born in January 1931 how old is he now?
Answer:
Step-by-step explanation:
He would be 87 years old right now
To determine Carl's age, we subtract his birth year, 1931, from the current year, 2022, resulting in Carl being 91 years old.
Explanation:To calculate how old Carl is now, you need to determine the current year and subtract Carl's birth year from it. Since Carl was born in January 1931, we would use 2022 as the current year (assuming it's the present year).
So, the calculation is simple: 2022 - 1931 = 91. Therefore, Carl would be 91 years old.
Learn more about Calculating Age here:https://brainly.com/question/20491616
#SPJ2
Simplify the expression (6^2)^4
Answer:
6^8 = 1,679,616
Step-by-step explanation:
The applicable rule of exponents is ...
(a^b)^c = a^(bc)
__
Applied to this problem, the rule tells you ...
(6^2)^4 = 6^(2·4) = 6^8 = 1,679,616
__
Or, you can evaluate the expression according to the Order of Operations:
(6^2)^4 = 36^4 = 1,679,616
Answer:
6^8 = 1,679,616
Step-by-step explanation:
i looked it up and i did it on my own
Your mother gave you $13.32 with which to buy a present. This covered 3/5 of the cost. How much did the present cost
Answer:
$22.20
Step-by-step explanation:
We are told that $13.32 only covered 3/5 of the cost. Does this mean it covered the whole cost? No. The 5 in the denominator represents the whole cost, and the 3 represents the fraction of the cost. In this case, 13.32 represents the 3, as it did not cover the whole cost.
Let's set up our equation by making 13.32 into a fraction.
13.32/x
We will represent the present's actual cost with the letter x.
13.32/x = 3/5
We want to make sure the 13.32 is in the numerator, equal to the 3 in the numerator in the 3/5 number, because we know that $13.32 only covered for a fraction of the present's cost, not the whole cost.
We solve this by doing cross multiplication. Multiply the 13.32 by the 5.
13.32 x 5 = 66.6
Next we divide 66.6 by 3 to get 22.2
66.6/3 = 22.2
This gives us our final answer of $22.20. This means that the cost of the original present was $22.20
The question involves setting up a proportion to find the total cost of the present. This was done step-by-step by dividing $13.32 by 3 to find 1/5 of the cost, and then multiplying by 5 to find the full cost. The present cost approximately $22.20
Explanation:The subject of your question is mathematics, particularly a topic in proportion. The information given is that $13.32 represents 3/5 of the cost of the present. We could set up a proportion to help calculate the full cost. If 3/5 is equal to $13.32, then 1 (or 5/5) would be equal to the full price of the present. We can solve for the full price by dividing $13.32 by 3 and then multiplying by 5 (since 5/5 represents the whole or full cost).
Step-by-step:
Divide $13.32 by 3. This gives you approximately $4.44, which represents the cost for 1/5 of the present. Multiply $4.44 by 5. This will give you the full cost of the present which is approximately $22.20.Learn more about Proportion here:https://brainly.com/question/31548894
#SPJ3